2017
DOI: 10.5578/keg.10401
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationship between Teachers’ Levels of Believe in Education and Work Engagement

Abstract: ABSTRACT:The purpose of the present study is to examine the relationship between teachers' levels of believe in education and work engagement. The study, designed as a correlational research, has a total of 220 teachers working in various public schools. The participants were surveyed by the "Teachers' Levels of Believe in Education Scale" developed by Akın and Yıldırım (2015) and "Work Engagement Scale" developed by Schaufeli, Salanova, González-Romá and Bakker (2002) originally and translated into Turkish by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
0
5
1
3
Order By: Relevance
“…Besides, Kavgacı (2014) and Köse (2015) have reached the conclusion that teachers' work engagement levels increase as their teaching experience increases. However, Gün (2017) has concluded that teachers' work engagement levels do not significantly vary across their seniority as in the present study.…”
Section: Result Discussion and Recommendationscontrasting
confidence: 53%
See 4 more Smart Citations
“…Besides, Kavgacı (2014) and Köse (2015) have reached the conclusion that teachers' work engagement levels increase as their teaching experience increases. However, Gün (2017) has concluded that teachers' work engagement levels do not significantly vary across their seniority as in the present study.…”
Section: Result Discussion and Recommendationscontrasting
confidence: 53%
“…The results of the research have revealed that the teachers' work engagement levels do not significantly differ across their gender, marital status, educational status and seniority. The studies conducted by Gün (2017), Kavgacı (2014), Köse (2015) and Sezen (2014) have shed light into the fact that teachers' work engagement levels do not significantly vary across their gender. Gün (2017) has found no significant difference in terms of marital status, while Sezen (2014) has identified that there is a statistically significant difference among teachers' perceptions towards the overall work engagement and dedication subscale in favor of married teachers.…”
Section: Result Discussion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations